2020
DOI: 10.3390/suschem1030017
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Cottonseed Protein Chemistry and Non-Food Applications

Abstract: There has been increasing interest in recent years in the use of agro-based raw materials for the production of bio-friendly and sustainable products. Plant-based proteins are among the popular materials being studied. In particular, cottonseed protein (a byproduct of cotton fiber production) is widely available and has useful properties. Although not as well-known as soy protein, cottonseed protein has been shown to be a potentially valuable raw material for numerous applications. In this review, the latest d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 117 publications
0
21
0
2
Order By: Relevance
“…Cottonseed protein (CSP) have been used for the formulation of biobased products [18][19][20], as animal feed [21,22], in films, coatings and adhesives [19]. Several proteins have been previously reported as binders and strength agents in paper products, such as soy protein [23][24][25][26][27], gelatin, zein, and hydroxyproline-rich glycoprotein [28] and cottonseed protein [29].…”
Section: Introductionmentioning
confidence: 99%
“…Cottonseed protein (CSP) have been used for the formulation of biobased products [18][19][20], as animal feed [21,22], in films, coatings and adhesives [19]. Several proteins have been previously reported as binders and strength agents in paper products, such as soy protein [23][24][25][26][27], gelatin, zein, and hydroxyproline-rich glycoprotein [28] and cottonseed protein [29].…”
Section: Introductionmentioning
confidence: 99%
“…These applications include packaging, adhesive, bioplastic, hydrogel, interfacial material, and emulsifying applications (Cheng et al, 2020). The application of CSP as a wood adhesive has been established in the recent past, and it has been reported that the combination of CSP and phosphoric acid is even more effective as a wood adhesive than soy protein .…”
Section: Nonfood Application Of Cottonseed Meal (Csm) and Cottonseed ...mentioning
confidence: 99%
“…Thus, it represents a valuable agro-industry biobased raw material with numerous applications due to its chemical composition (fibers, proteins, carbohydrates, and lipids) [119]. In terms of amino acid composition, it has nearly the same primary amino acid components as soy protein, those with the highest levels being arginine, glutamic acid, and glutamine [120].…”
Section: Cotton Proteinmentioning
confidence: 99%